Comparative proteomics analysis provide novel insight into laminitis in Chinese Holstein cows - Dong, Shu-Wei (BMC Vet Res, 2015)
BACKGROUND: Laminitis is considered as the most important cause of hoof lameness in dairy cows, which causes abundant economic losses in husbandry. Through intense efforts in past decades, the etiology of laminitis is preliminarily considered to be subacute ruminal acidosis; however, the pathogenesis of laminitis needs further research. The differentially expressed proteins (DEP) were detected in plasma of healthy cows and clinical laminitis cows by two-dimensional gel electrophoresis (2-DE) and identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. RESULTS: Nineteen protein spots were differentially expressed, and 16 kinds of proteins were identified after peptide mass fingerprint search and bioinformatics analysis. Of these, 12 proteins were differentially up-regulated and 4 down-regulated. Overall, these differential proteins were involved in carbohydrate metabolism, lipids metabolism, molecular transport, immune regulation, inflammatory response, oxidative stress and so on. CONCLUSIONS: The DEPs were closely related to the occurrence and development of laminitis and the lipid metabolic disturbance may be a new pathway to cause laminitis in dairy cows. The results provide the theory foundation for further revealing the mechanism of laminitis and screening the early diagnostic proteins and therapeutic target.